DEMOGRAPHIC SITUATION OF SIRDARYA REGION AND ITS GEOGRAPHICAL ASPECTS (Scientific journal of the Fergana State University, 2023)
Demographic processes and their territorial characteristics are defined in the article. The main focus is on birth and death rates. There are differences in the birth and death rates of Syrdarya region in different regions. At the same time, differences in the death rate for various reasons have been identified.